2015
DOI: 10.1111/jsap.12335
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneaous linear gastric tears in a cat

Abstract: An 11-year-old female cat presented for chronic vomiting. Endoscopy revealed an altered gastric mucosa and spontaneous formation of linear gastric tears during normal organ insufflations. The histopathological diagnosis was atrophic gastritis with Helicobacter pylori infection. Medical treatment permitted a complete resolution of clinical signs. The linear tears observed resembled gastric lesions rarely reported in humans, called "Mallory-Weiss syndrome". To the authors' knowledge this is the first report of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The potential of identifying a gastric tumour on radiographs depends on multiple variables, including tumour size, discrete mass vs diffuse lesion, and the presence of luminal gas providing spontaneous contrast. 24 While radiography has been largely replaced by ultrasound, endoscopy and, more recently, CT in the diagnostic work-up of gastric neoplasia in veterinary patients, 25 our results support its value as a screening tool. Conventional radiography is inexpensive, widely available and should be considered a valid initial test when gastric neoplasia is clinically suspected, especially in clinical settings where US evaluation is not readily available.…”
Section: Discussionmentioning
confidence: 53%
“…The potential of identifying a gastric tumour on radiographs depends on multiple variables, including tumour size, discrete mass vs diffuse lesion, and the presence of luminal gas providing spontaneous contrast. 24 While radiography has been largely replaced by ultrasound, endoscopy and, more recently, CT in the diagnostic work-up of gastric neoplasia in veterinary patients, 25 our results support its value as a screening tool. Conventional radiography is inexpensive, widely available and should be considered a valid initial test when gastric neoplasia is clinically suspected, especially in clinical settings where US evaluation is not readily available.…”
Section: Discussionmentioning
confidence: 53%
“…[15][16][17] Pyloric adenocarcinomas are usually annular and stenosing. 14 In this study, adenocarcinomas were found to form thickening lesions that involved the outer layer. In previous report, gastric adenocarcinomas display diffuse or segmental wall thickening lesion.…”
Section: Discussionmentioning
confidence: 69%
“…Adenomas are polypoid masses composed of moderately atypical glandular epithelium surrounded by lamina propria. 14 Adenomas present features of nonneoplastic lesions that include hypertrophic gastritis and hyperplastic polyps. 14 In dogs, adenocarcinoma is malignant and epithelial in origin, infiltrates submucosal areas, and is often located in small curvatures and pylori.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations